Radiofrequency Ablation for Colorectal Cancer Liver Metastases: Outcomes and Prognostic Factors Associated with Survival - Akhan, Okan; Akçalar, Seray; Ünal, Emre; Metin, Yavuz; Çiftçi, Türkmen; Akıncı, Devrim (Turkish Journal of Gastroenterology, 2023)
Background: To determine the long-term outcomes of radiofrequency ablation with respect to overall survival, disease-free survival, and complications in patients with colorectal cancer liver metastases. Additionally, we sought to examine whether various patient- and treatment-related characteristics were associated with prognosis. Methods: Fifty-nine patients with colorectal cancer liver metastases who had undergone percutaneous radiofrequency ablation treatment were included in this study. A total of 138 lesions were treated with radiofrequency ablation in the first and second sessions. Tumor diameters ranged from 10 to 60 mm (mean, 2.45 mm). Treatment efficacy, complications, and overall survival and disease-free survival were analyzed. Results: The primary success rate of radiofrequency ablation was 94.4%. At the end of the first month, the residual disease was detected in 12 lesions, 10 of which underwent secondary radiofrequency ablation treatment, resulting in a cumulative secondary success rate of 98.4%. The 1-, 3-, and 5-year overall survival rates in 59 patients with colorectal cancer liver metastases were 94.9%, 52.5%, and 40.6%, respectively. The median survival was 42 months in patients with metastasis size of ≤3 cm, while it was 25 months in patients with metastasis size of >3 cm (P = .001). The 1-, 3-, and 5-year disease-free survival rates were 44%, 10.2%, and 6.7%, respectively. Metastatic tumor status (solitary or multiple) was a significant prognostic factor in determining overall survival and disease-free survival; furthermore, extrahepatic recurrence during follow-up was a prognostic factor affecting overall survival. Minor complications developed in four radiofrequency ablation procedures (6.7%). Conclusion: Radiofrequency ablation remains a safe and effective treatment option improving survival in select cases of colorectal cancer liver metastases.